The Role of Accounting in Sustainability and Corporate Social Responsibility: Accounting for a Better Future - Gulo, Marnila; Octafian, Ray (Penelitian dan Pengembangan Ilmu, 2024)
This research presents a systematic synthesis of the role of accounting in advancing sustainability and corporate social responsibility (CSR) based on extensive discussion in the literature. Through analysis of stakeholder perspectives, investor expectations, regulatory frameworks, employee expectations, community involvement, accounting practices, challenges, future directions, and the role of developing technology and collaborative efforts, this research concludes that accounting has a crucial role in promoting sustainable business practices and responsibility. Key findings suggest that integration of diverse viewpoints, investor needs, a strong regulatory framework, meeting employee expectations, effective community engagement, prudent accounting practices, as well as adoption of emerging technologies and collaborative efforts are key in driving sustainability and CSR initiatives. This research also identifies the limitations of current accounting practices and proposes future research directions to enhance the role of accounting in promoting sustainability and corporate social responsibility.